Yehuda Bauer: A Legacy of Holocaust and Genocide Studies - Dreyfus, Ḥaṿi (Holocaust and genocide studies, 2025)
Yehuda Bauer, the founding editor of Holocaust and Genocide Studies, passed away on October 18, 2024, at the age of ninety-eight, signifying the loss of an